2012
DOI: 10.1186/1471-244x-12-97
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the expression of depression and distress in aboriginal men in central Australia: a qualitative study

Abstract: BackgroundDespite being at heightened risk of developing mental illness, there has been little research into the experience of depression in Australian Aboriginal populations. This study aimed to outline the expression, experience, manifestations and consequences of emotional distress and depression in Aboriginal men in central Australia.MethodsUtilizing a grounded theory approach, in depth semi-structured interviews were conducted with 22 theoretically sampled young, middle aged and senior Aboriginal men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 25 publications
(28 reference statements)
2
66
0
Order By: Relevance
“…Given the substantial differences in culture and community between Aboriginal Australians and the non-Aboriginal population, community-specific and culturally appropriate strategies are needed to promote screening for depression in Aboriginal patients with type 2 diabetes [39]. Identification of the potentially large proportion of patients with unrecognised or untreated or under-treated depression should be linked with a detailed assessment of alcohol use, smoking habit and cardiovascular risk factors which are likely to be relatively adverse but modifiable [40].…”
Section: Discussionmentioning
confidence: 99%
“…Given the substantial differences in culture and community between Aboriginal Australians and the non-Aboriginal population, community-specific and culturally appropriate strategies are needed to promote screening for depression in Aboriginal patients with type 2 diabetes [39]. Identification of the potentially large proportion of patients with unrecognised or untreated or under-treated depression should be linked with a detailed assessment of alcohol use, smoking habit and cardiovascular risk factors which are likely to be relatively adverse but modifiable [40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on socially disadvantaged or marginalized groups reported on further social factors contributing to depression: in a study on depression in Aboriginal men in Australia, depression appeared as a consequence of "recurrent, cumulative stress, disadvantage, marginalization, oppression, forced separation and an overwhelming sense of loss" [45] . In US-based studies, African-American men reported on the consequences of sociostructural factors such as unemployment, homelessness, racism, and sexism on their mental health [23,46] .…”
Section: Semistructured Interviewsmentioning
confidence: 99%
“…The three dental behaviour variables were toothbrush ownership (yes, no), brushing teeth the previous day (yes, no) and toothpaste use (yes, no). The three psychological health variables were scared of dentist (little bit, fair bit or heaps vs no), psychological distress as measured by a modified Kessler-6 (K6) instrument for use among Aboriginal Australians and psychological distress as measured by a modified Patient Health Questionnaire-9 (PHQ-9) instrument for use among Aboriginal Australians 12,13 . The sum of each scale was calculated to create mean scores, with each scale score then trichotomised into 'low', 'moderate' or 'high' groups.…”
Section: Accepted Articlementioning
confidence: 99%